QUALITY IN MEDICINEAnalysis of the subjective assessment of the “Periprocedural safety checklist for patients referred to the hemodynamic and electrotherapy laboratories” by employees of the cardiology department and the hemodynamic laboratory of the Silesian Center for Heart Diseases - Czapla, Krystyna; Gąsior, Mariusz; Hawranek, Michał; Pudlo, Robert; Cieśla, Daniel; Nowowiejska-Wiewióra, Alicja; Gierlotka, Marek; Szafranek, Andrzej; Poloński, Lech; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Background : Checklists are used in various fields of science; in medicine, their use in surgery is recommended by the WHO. There are no studies on the use of checklists in interventional cardiology. The aim of the study was to analyze the subjective assessment of the periprocedural safety checklist by the employees of the departments of cardiology and hemodynamics. Material and methods : Members of the medical staff directly involved in fulfilling the checklist items were included in a diagnostic survey and asked to evaluate the periprocedural safety checklist by means of a questionnaire. A total of 31 doctors, 46 nurses, and 8 medical technicians participated in the study. Results: In the opinion of the medical staff, the procedural checklist improved internal communication and enhanced workflow in the cardiology and hemodynamics departments; it also prevents medical errors and reduces the incidence of periprocedural complications. A significant portion of the staff believes that the introduction of the checklist facilitates providing periprocedural care to the patient and improves the quality of medical care and nursing. The periprocedural safety checklist specifies the tasks to be completed and defines staff responsibilities. In the opinion of the medical staff, the introduction of the checklist is justified. Conclusions : The introduction of the periprocedural safety checklist was the correct step, serving to improve the quality of care for patients undergoing invasive diagnostic and therapeutic procedures in the departments of cardiology and electrotherapy. It is a simple tool for reducing periprocedural complications, aiding the medical staff in providing proper patient care. The introduction of the cardiac checklist was well founded and well understood by the treatment team.